Porous composite elastic film with excellent stress resistance and method for producing the same
Patent Information
- Application Number
- KR1020250023994
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2026-09-01
Smart Images

Figure PAT00003_ABST
Abstract
Description
Technology Field
[0001] The object of the present invention is to a porous composite elastic film with excellent stress and a method for manufacturing the same. Background Technology
[0002] All-solid-state batteries are next-generation battery technology that uses solid electrolytes to enhance safety and energy density, and applying high voltage is crucial during the manufacturing and formation process of these batteries.
[0003] Improving the adhesion between the solid electrolyte and the electrode is crucial for optimizing the performance of all-solid-state batteries; therefore, high pressure is applied to ensure the electrolyte and electrode adhere closely, thereby maintaining a smooth and uninterrupted conduction pathway within the battery.
[0004] All-solid-state batteries can ensure structural stability through pressure. The pressure applied during the formation process reduces internal cracks or voids, thereby extending the battery's lifespan.
[0005] All-solid-state batteries require a solid electrolyte of uniform thickness. By applying pressure to form a uniform thickness, consistent performance between cells can be maintained.
[0006] In the manufacturing of all-solid-state batteries, this high-pressure process is a core technology that improves the battery's stability, efficiency, and lifespan, and the process of applying this high pressure is carried out using specialized equipment.
[0007] In addition, in stacked solid-state batteries, as charge and discharge cycles are repeated, each individual cell undergoes expansion and contraction, causing pressure changes between adjacent cells. The degree of expansion or contraction of each cell is not completely uniform and tends to be concentrated in the plane of the stacked layer (perpendicular to the stacking direction). This results in uneven pressure being applied to each cell along the stack plane.
[0008] Therefore, due to repeated charging and discharging, an unstable interface between the anode layer and the anode current collecting foil of each cell, or a crack formed between the anode layer and the solid electrolyte layer, may occur, resulting in a defect that can cause a short circuit.
[0009] Accordingly, the inventors have completed the present invention by developing an elastic film with excellent stress resistance that prevents defects caused by short circuits resulting from crack formation, which ensures stable operation of a stacked solid-state battery by introducing a buffer layer between individual cells to alleviate pressure concentration during charging and discharging cycles. The problem to be solved
[0010] The object of the present invention is a hybrid polymer;
[0011] Silroksan;
[0012] Isonate-based curing agent;
[0013] Crosslinking agent; and
[0014] Catalyst; including,
[0015] The above hydropolymer comprises one or more from the group consisting of acrylic polymer resin, Si polymer (Si Polymer), polymer (Polyol), PU, and silicone.
[0016] The invention provides a porous composite elastic film containing porous cells with a right-angled cross section.
[0017] In addition, the objective of the present invention is (a) a step of first mixing a hydropolymer, a curing agent, and an isocyanate;
[0018] (b) A step of performing a second mixing step by adding a catalyst and a crosslinking agent after the first mixing step of (a) above;
[0019] (c) a step of visually confirming and casting the porous cells of the secondary mixture of (b) above; and
[0020] (d) a step of manufacturing a film using a roll-to-roll method after step (c) above; the present invention provides a method for manufacturing a porous elastic sheet composition comprising means of solving the problem
[0021] The present invention relates to a hybrid polymer;
[0022] Silroksan;
[0023] Isonate-based curing agent;
[0024] Crosslinking agent; and
[0025] Catalyst; including,
[0026] The above hydropolymer comprises one or more from the group consisting of acrylic polymer resin, Si polymer (Si Polymer), polymer (Polyol), PU, and silicone.
[0027] A porous composite elastic film containing porous cells with a right-angled cross section is provided.
[0028] In addition, the present invention comprises (a) a step of first mixing a hydropolymer, a curing agent, and an isocyanate;
[0029] (b) A step of performing a second mixing step by adding a catalyst and a crosslinking agent after the first mixing step of (a) above;
[0030] (c) a step of visually confirming and casting the porous cells of the secondary mixture of (b) above; and
[0031] (d) a step of manufacturing a film using a roll-to-roll method after step (c); the present invention provides a method for manufacturing a porous elastic sheet composition comprising the above steps. Effects of the invention
[0032] The present invention has confirmed that a porous composite elastic film composed of a hydropolymer controls the size of open cells and closed cells, which are porous cells with a right cross-section, and the size of stress release holes on the film surface according to the ratio of a curing agent and a catalyst. In addition, it has been confirmed that the porous composite elastic film of the present invention has superior resilience and electrical conductivity compared to other films, and thus can be usefully applied in related businesses. Brief explanation of the drawing
[0033] Figure 1 is a diagram showing the process of manufacturing a porous composite elastic film of the present invention. Figure 2 is a figure showing the hysteresis test process of the porous composite elastic film of the present invention. Figure 3 is a figure showing the stress-restoring force of the porous composite elastic film, SI Foam, and PU Foam of the present invention. FIGS. 4 to 6 are figures showing the open cell / closed cell of a right-angle cross-section and the stress release hole size on the film surface according to the ratio of the curing agent and catalyst included in the porous composite elastic film of the present invention. Figure 7 is a figure showing the increase in hardness according to the concentration added to the curing agent of the porous composite elastic film of the present invention. Figure 8 is a figure showing the hardness and hysteresis according to the ratio of acrylic polymer addition of the porous composite elastic film of the present invention. Specific details for implementing the invention
[0034] Specific embodiments of the present invention will be described in detail below with reference to the drawings. However, the concept of the present invention is not limited to the presented embodiments. Those skilled in the art who understand the concept of the present invention may easily propose other inventions that are inferior or other embodiments included within the scope of the concept of the present invention by adding, changing, or deleting other components within the same scope of the concept, and such are also to be considered to be included within the scope of the concept of the present invention.
[0035] Additionally, the terms used in this invention are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. Throughout the specification of this invention, the term 'comprising' any component means that, unless specifically stated otherwise, it does not exclude other components but may include additional components. The invention will be described in detail below.
[0036] All technical terms used in this invention, unless otherwise defined, are used in the sense generally understood by those skilled in the art in the relevant field of this invention. Furthermore, while preferred methods or feeds are described herein, similar or equivalents are also included within the scope of this invention. The contents of all publications cited as references in this specification are incorporated into this invention.
[0037] Throughout this specification, '%' used to indicate the concentration of a particular substance is (w / w) % for solid / solid, (w / v) % for solid / liquid, and (v / v) % for liquid / liquid, unless otherwise noted.
[0038] The present invention relates to a hybrid polymer;
[0039] Silroksan;
[0040] Isonate-based curing agent;
[0041] Crosslinking agent; and
[0042] Catalyst; including,
[0043] The above hydropolymer comprises one or more from the group consisting of acrylic polymer resin, Si polymer (Si Polymer), polymer (Polyol), PU, and silicone.
[0044] A porous composite elastic film containing porous cells with a right-angled cross section is provided.
[0045] In one embodiment, the isonate-based curing agent may comprise one or more from the group consisting of MDI (Methylene Diphenyl Diisocyanate), TDI (Toluene Diisocyanate), HDI (Hexamethylene Diisocyanate), IPDI (Isophorone Diisocyanate), and XDI (Xylylene Diisocyanate), but is not limited thereto.
[0046] Specifically,
[0047]
[0048] MDI and TDI can be mixtures of isomers. For example, a mixture of 2,4'-MDI isomers, 2,2'-MDI, and 4,4'-MDI isomers can be used. Also, a mixture of 2,4-TDI (toluene diisocyanate) isomers and 2,6-TDI isomers was used.
[0049] As the above crosslinking agent, a polyfunctional substance with three or more functionalities may be used, for example, diethanolamine (DEOA), triethanolamine (TEOA), glycerin, DPG, 1.4BDO, etc. may be used as a crosslinking agent.
[0051] In one embodiment, the acrylic polymer resin may comprise one or more of the group consisting of butyl acrylate (BA), isocyanatoethyl acrylate (ICBA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl acrylate (HPA), methyl methacrylate (MMA), ethyl acrylate (EA), acrylonitrile (AN), methyl acrylate (MA), and acrylic acid (AA), but is not limited thereto.
[0052] In one embodiment, the siloxane may include one or more from the group consisting of organo siloxane, cyclo siloxane, linear siloxane, poly siloxane, alkoxy siloxane, amino siloxane, phenyl siloxane, and vinyl siloxane, but is not limited thereto.
[0053] In one embodiment, the catalyst may include an organometallic catalyst or an amine catalyst, but is not limited thereto.
[0054] The above organometallic catalyst may include one or more elements from the group consisting of bismuth, potassium, tin, iron (Fe), and nickel (Ni).
[0055] The above amine catalysts are ethylamine (C2H5NH₂), propylamine (C2H7NH₂), methylamine (CH3NH₂), diethylamine ((C2H5)₂NH), dipropylamine ((C3H7)₂NH), dimethylamine ((CH3)₂NH), triethylamine ((C2H5)₃N), N,N-dimethylcyclohexylamine (C5H₁7N), N,N-dimethylethylenediamine ((CH3)₂NCH₂CH₂N(CH₃)₂), benzyltrimethylammonium chloride (C9H₁₄NCl), and tetramethylammonium chloride. It may include one or more from the group consisting of (CH3)₄NCl), tetraethylammonium bromide ((C2H5)₄NBr), ammonium chloride (NH4Cl), ammonium nitrate (NH4NO₃), and ammonium sulfate ((NH4)₂SO₄).
[0056] In one embodiment, the thickness of the porous sheet composition may be 10 to 3000 μm, but is not limited thereto, and preferably may be 50 to 800 μm.
[0057] In one embodiment, the equivalent amount of the isonate-based curing agent of the porous composite elastic film may be 110 to 150 g / eq or less, but is not limited thereto.
[0058] In one embodiment, the catalyst of the porous composite elastic film may be included in a weight ratio of 0.1 to 0.001 relative to the isonate-based curing agent, but is not limited thereto.
[0059] The above catalyst has a difference in the number of closed cells or open cells depending on the addition ratio.
[0060] As the catalyst increases, the curing reaction of the polymer accelerates, and the foam quickly hardens in a solid state. Consequently, air or gas is completely trapped, leading to an increase in closed-cell structures with no internal voids.
[0061] In addition, as the catalyst decreases, the reaction rate slows down, ensuring sufficient time for the bubbles to expand; during this process, the bubbles burst and connect with the air, increasing the open-cell structure.
[0062] In one embodiment, the hydropolymer may comprise 1 to 20% acrylic polymer, 30 to 50% Si polymer (Si Polyoli) and polyol (Polyol), and 10 to 30% silicone, but is not limited thereto.
[0063] In one embodiment, the porous cells of the right-angled cross-section may include closed cells or open cells, but are not limited thereto.
[0064] The diameter of the closed cell may be 50 to 200 μm, and the diameter of the open cell may be 10 to 40 μm.
[0065] The porous cells of the above-mentioned right-angled cross-section may be closed cells or open cells.
[0066] In the present invention, a "right-angle cross-section" is defined as a surface cut at a 90-degree angle when a porous sheet composition is placed on a flat surface.
[0067] In the present invention, the "closed cell" is characterized by having a cell that is completely filled without any empty space, and as the volume of the closed cell increases, the shock absorption efficiency increases.
[0068] In the present invention, an "open cell" is a cell with an empty space inside, and has the characteristic that electrical conductivity efficiency increases as the volume of the open cell increases.
[0069] The diameter of the closed cell is 50 to 200 μm and the diameter of the open cell is 10 to 40 μm, but is not limited thereto. Preferably, the diameter of the closed cell may be 120 to 210 μm and the diameter of the open cell may be 15 to 27 μm.
[0070] The surface of the porous composite elastic film may also include a plurality of stress release holes.
[0071] In one embodiment, the diameter of the opening of the stress release hole may be 3 to 80 μm, but is not limited thereto.
[0072] The above-mentioned porous composite film surface includes a plurality of stress release holes, wherein a stress release hole is a hole open on the surface of the porous sheet composition of the present invention through which stress is released, and stress release capability can be improved through a plurality of stress release holes.
[0073] In addition, the larger the size of the stress release hole, the more the stress can be distributed over a wide area, and the hardness can be prevented from decreasing rapidly.
[0074] Furthermore, when the film is compressed or bent, it can flexibly deform around the hole, which may increase its resistance to specific loads while maintaining a rigid feel.
[0075] Accordingly, the diameter of the opening of the stress release hole is 3 to 80 μm, but is not limited thereto, and preferably may be 5 to 70 μm.
[0077] The above-mentioned foam stabilizer may be included for the purpose of maintaining the homogeneity of the foaming mixture and maintaining the bubble cell structure so that the bubbles can be formed stably without being destroyed even if they expand rapidly during foaming. The above-mentioned foam stabilizer may be a conventional one. For example, a silicone-based foam stabilizer or a fluorine-containing compound-based foam stabilizer may be used.
[0078] Among these foaming agents, silicone-based foaming agents with strong foaming power can be used to form good bubbles.
[0079] Specifically, in the present invention, silicone polyther brached copolymers were used.
[0080] The above polymer (Polyol) can control soft / hard properties by controlling the molecular weight (degree of polymerization).
[0081] The above acrylic polymer resin can have tough, hard, or soft properties depending on the type.
[0082] The above isocyanate reacts with polyols, polymers, and chain extenders to control properties such as hardness, elongation, and strength depending on the type and composition ratio.
[0083] The thickness of the porous sheet composition may be 10 to 3000 μm, but is not limited thereto, and preferably may be 50 to 800 μm.
[0084] If the thickness of the porous sheet composition is less than 10 μm, the impact resistance and resilience are reduced, and if it exceeds 3000 μm, it is difficult to obtain further increases in resilience, and it is too thick, making adhesion between objects difficult and causing economic losses.
[0085] The above-mentioned porous composite film surface includes a plurality of stress release holes, wherein a stress release hole is a hole open on the surface of the porous sheet composition of the present invention through which stress is released, and stress release capability can be improved through a plurality of stress release holes.
[0086] Accordingly, the diameter of the opening of the stress release hole is 3 to 80 μm, but is not limited thereto, and preferably may be 5 to 70 μm.
[0088] The present invention comprises (a) a step of first mixing a hydropolymer, a curing agent, and an isocyanate;
[0089] (b) A step of performing a second mixing by adding a catalyst and a crosslinking agent after the first mixing of step (a) above;
[0090] (c) a step of visually confirming and casting the porous cells from the secondary mixture of step (b) above; and
[0091] (d) the step of (c) above; and thereafter, the step of manufacturing a film using a roll-to-roll method; the present invention provides a method for manufacturing a porous composite elastic film.
[0092] In one embodiment, the secondary mixing of step (b) may be to make the material uniform.
[0093] In one embodiment, the product may be manufactured in the form of a thin film after casting in step (c).
[0095] The present invention will be explained in more detail below through the following manufacturing examples and embodiments. However, the following embodiments are merely examples to easily explain the content and scope of the technical concept of the present invention, and the technical scope of the present invention is not limited or altered by these examples. Furthermore, it can be easily determined by those skilled in the art that various modifications and changes are possible within the scope of the technical concept of the present invention based on these examples.
[0097] Preparation Example 1. Method for manufacturing a porous composite elastic film of the present invention
[0098] To manufacture the porous composite elastic film of the present invention, first, as follows A hybrid polymer with a weight-average molecular weight of 80,000 to 100,000 was prepared. The hydropolymer consists of 1 to 20% acrylic polymer, 30 to 50% Si polymer (Si Polyoli) and polyol (Polyol), and 10 to 30% silicone.
[0099] In contrast to hydropolymers 4 to 8 parts by weight of siloxane, 3 to 6 parts by weight of foaming agent ...was added and the hydropolymer By adding an isocyanate curing agent at an equivalent weight of 110 g / eq or more and 150 g / eq A mixture was prepared by uniformly mixing in the first step.
[0100] Afterwards, to the first mixture 7 to 12 parts by weight of a cross-linking agent, and a catalyst added in a range of 0.1 to 0.0001 relative to the isocyanate curing agent. Thus, a second mixing step was performed. In the second mixing step, the mixture was mixed sufficiently to ensure proper mixing, thereby maintaining a uniform porous structure and physical properties.
[0101] .
[0102] Once the second mixture is completed, it is cast to form a film. To confirm that porosity was imparted during the casting process, a right-angle cross-section can be visually inspected using a microscope. To control the porosity of the right-angle cross-section, the second mixture was cast by setting a density of 0.5 to 0.8 g / cm³ under conditions of 80°C and 0.2 MPa.
[0103] A film was manufactured by processing the cast secondary mixture using a roll-to-roll method. At this time, the film thickness was manufactured to be 50 to 800 μm to produce the porous composite elastic film of the present invention with optimized electrical conductivity and impact resistance.
[0105] Example 1. Characteristics of the porous composite elastic film of the present invention
[0106] To confirm the characteristics of the porous composite elastic film of the present invention, PU Foam, SI Foam, and the porous sheet composition of the present invention were compared and prepared in Table 1 below.
[0107] PU Foam SI Foam porous film ingredient Polyurethane Silicon rubber Hybrid material thickness 0.08 ~ 3 T 0.1 ~ 5T 0.05 ~ 3T density 0.2 ~ 0.9 0.1 ~0.5 0.3 ~ 0.9 hardness < 60 < 40 > 60 CFD 25% 0.015 ~ 0.15 0.02 ~ 0.20 0.015 ~ 0.10 Compressive deformation > 30 > 90 > 90 Maximum strain > 90 > 90 > 90 sealing 60 70 90 Dimensional stability 70 60 90
[0108] As shown in Table 1, compared to PU Foam and SI Foam, the porous composite elastic film of the present invention has excellent power and viscosity, excellent hysteresis and compressive strain, and excellent maximum strain and sealing properties.
[0109] Furthermore, since it was confirmed that the porous composite elastic film of the present invention exhibits the highest stability, it can be used stably without dimensional changes; thus, it was confirmed that the porous composite elastic film of the present invention is a highly stable material that can be used in fields requiring various pressures and elasticity.
[0111] Example 2. Confirmation of the resilience of the porous composite elastic film of the present invention
[0112] To confirm that the porous composite elastic film of the present invention has excellent resilience, the elastic film of the present invention, SI foam, and PU foam, each measuring 25 x 25 mm and 10 mm (10T) in thickness, were mounted on a universal testing machine (UTM) and compressed by applying a load (Fig. 2).
[0114] Example 2-1. Initial load setting (0.02 kgf)
[0115] Before starting the compression, on the Psalm 0.02 kgf An initial load was applied to ensure the specimen was stably positioned on the compression jig. The initial load serves to lightly press the specimen to fix its position.
[0117] Example 2-2. 25% compression load setting (1 kgf)
[0118] Thickness criteria for each material after initial loading 25% compression state So that it becomes 1 kgf A load was applied. At this stage, the partial compression state of the specimen was checked, and the durability and compression characteristics of the specimen were verified.
[0120] Example 2-3. 50% compression load setting (4 kgf)
[0121] Finally, the thickness of each material Compress up to 50% so 4 kgfA load was applied. At this stage, the material was compressed by about half, and preparations were made to measure the restoring force of the specimen after 50% compression. The load was removed from the 50% compression state, and the process of each material returning to its original thickness was observed.
[0123] In this process, the resilience of the porous composite elastic film of the present invention was measured. The resilience is For elastic films, 30% or less , For SI and PU foams, over 80% It was confirmed that it was.
[0125] As a result, it was confirmed that the porous composite elastic film of the present invention has the lowest hysteresis (Good Hysteresis) and the best resilience (Fig. 3).
[0127] Example 3. Confirmation of open cell / closed cell size control according to the curing agent concentration of the porous composite elastic film of the present invention
[0128] It was confirmed that the open cell / closed cell size of the right-angle cross-section and the size of the stress release holes on the surface of the porous composite elastic film of the present invention can be controlled according to the concentration of the added curing agent.
[0129] Specifically, the open-cell / closed-cell size of the right-angle cross-section of the porous composite elastic film varies depending on the curing speed and the temperature and curing agent concentration; therefore, the open-cell / closed-cell size of the right-angle cross-section was controlled by fixing the temperature condition and varying the curing agent concentration.
[0130] division hardener Open Cell Closed cell Surface (stress release hole size) M1 51.9 33.3 um 159 um 11.9~69.0 um M2 48.5 21.9 um 155 um 6.29~43.8 um M3 38.1 15.6 um 100 µm 11.6~47.5 um
[0131] According to Table 2 above, it was confirmed that the size of open cells / closed cells is controlled by fixing the curing speed and manufacturing temperature when manufacturing the porous film of the present invention and adjusting the addition concentration according to the curing agent (Figs. 4 to 6).
[0132] In addition, it was confirmed that the hardness increases as the concentration of the curing agent added to the porous composite elastic film of the present invention increases (Fig. 7).
[0134] Example 4. Confirmation of shock absorption according to the concentration of curing agent added to the porous composite film of the present invention
[0135] The closed cell size of the porous composite film of the present invention depends on the concentration of the added curing agent.
[0136] M1, M2, and M3 of Table 2 of Example 3 above were each manufactured with dimensions of 10 cm x 10 cm x 0.8 mm (thickness).
[0137] A 10kg round weight was prepared and dropped from a height of 50cm onto M1, M2, and M3 respectively. After impact, the thicknesses of M1, M2, and M3 were measured, and the initial thickness and the thickness after impact were compared. The strain was then measured according to the following mathematical formula 1 to confirm the shock absorption effect.
[0138] [Mathematical Formula 1]
[0139]
[0140] Initial thickness (mm) Thickness after impact (mm) Strain (%) M1 0.8 0.72 10 M2 0.8 0.68 15 M3 0.8 0.60 25
[0141] As shown in Table 3 above, it was confirmed that the shock absorption effect was relatively low because the strain of M3 was the highest, and the shock absorption effect was the best because the strain of M1 was the lowest, confirming that the shock absorption effect is better as the closed cell size increases.
[0143] Example 5. Confirmation of Hardness and Hysteresis According to the Addition Ratio of Acrylic Polymer in the Porous Composite Film of the Present Invention
[0144] Hardness and hysteresis were confirmed according to the ratio of acrylic polymer addition in the porous composite film of the present invention.
[0145] Acrylic polymer addition ratio Hysteresis Hardness 0% 30 ~ 40 % 60 ~ 80 1~5% 20 ~ 30 % 70 ~ 90 5~10% 5 ~ 20 % 75 ~ 95 10~15% 10 ~ 25 % 65 ~ 85
[0146] As shown in Table 4 above, the hydropolymer was prepared with varying acrylic polymer addition ratios of 1–5%, 5–10%, and 10–15%, and the silicon addition ratio was adjusted according to the acrylic polymer addition ratio in proportion to the total weight of the hydropolymer. When hardness and hysteresis were checked in Table 4 above, it was confirmed that the slope of the stress-strain curve and the maximum stress increased as the acrylic polymer addition ratio of the hydropolymer increased. This suggests that the hardness and hysteresis of the material increase as the acrylic polymer concentration increases.
[0147] In other words, it suggests that as the concentration of acrylic polymer increases, the material becomes stronger and the energy loss during restoration after deformation is greater.
[0148] Accordingly, it was confirmed that the concentration of 5 to 10% acrylic polymer added to the hydropolymer of the present invention provides the best elasticity and resilience performance and efficiency (Fig. 8).
[0150] Although the present invention has been described in detail with reference to preferred embodiments, the scope of the technical concept of the present invention is not limited to these embodiments. Accordingly, various modifications or equivalent embodiments may exist within the scope of the technical concept of the present invention. Therefore, the scope of rights regarding the technical concept according to the present invention should be interpreted by the claims, and technical concepts within an equivalent or equivalent scope should be interpreted as falling within the scope of rights regarding the present invention.
Claims
Claim 1 A porous composite elastic film comprising a hydropolymer (hybrid polymer); siloxane; an isonate-based curing agent; a crosslinking agent; and a catalyst; wherein the hydropolymer comprises one or more selected from the group consisting of acrylic polymer resin, Si polymer (Si Polymer), polymer (Polyol), PU, and silicone, and comprising porous cells with a right-angled cross section. Claim 2 A porous composite elastic film according to claim 1, wherein the isonate-based curing agent comprises one or more selected from the group consisting of MDI (Methylene Diphenyl Diisocyanate), TDI (Toluene Diisocyanate), HDI (Hexamethylene Diisocyanate), IPDI (Isophorone Diisocyanate) and XDI (Xylylene Diisocyanate). Claim 3 A porous composite elastic film according to claim 1, wherein the acrylic polymer resin comprises one or more of the group consisting of butyl acrylate (BA), isocyanatoethyl acrylate (ICBA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl acrylate (HPA), methyl methacrylate (MMA), ethyl acrylate (EA), acrylonitrile (AN), methyl acrylate (MA), and acrylic acid (AA). Claim 4 A porous composite elastic film according to claim 1, wherein the siloxane comprises one or more selected from the group consisting of organo siloxane, cyclo siloxane, linear siloxane, poly siloxane, alkoxy siloxane, amino siloxane, phenyl siloxane, and vinyl siloxane. Claim 5 In claim 1, the catalyst is a porous composite elastic film comprising an organometallic catalyst or an amine catalyst. Claim 6 In claim 5, the organometallic catalyst comprises one or more elements from the group consisting of bismuth, potassium, tin, iron (Fe), and nickel (Ni), forming a porous composite elastic film. Claim 7 In claim 5, the amine catalyst is ethylamine (C2H5NH₂), propylamine (C2H7NH₂), methylamine (CH3NH₂), diethylamine ((C2H5)₂NH), dipropylamine ((C3H7)₂NH), dimethylamine ((CH3)₂NH), triethylamine ((C2H5)₃N), N,N-dimethylcyclohexylamine (C5H₁7N), N,N-dimethylethylenediamine ((CH3)₂NCH₂CH₂N(CH₃)₂), benzyltrimethylammonium chloride (C9H₁₄NCl), and tetramethylammonium salt A porous composite elastic film comprising one or more from the group consisting of (Tetramethylammonium chloride, (CH3)₄NCl), tetraethylammonium bromide (Tetraethylammonium bromide, (C2H5)₄NBr), ammonium chloride (Ammonium chloride, NH4Cl), ammonium nitrate (Ammonium nitrate, NH4NO₃), and ammonium sulfate (Ammonium sulfate, (NH4)₂SO₄). Claim 8 A porous composite elastic film according to claim 1, wherein the thickness of the porous composite elastic film is 10 to 3000 μm. Claim 9 A porous composite elastic film comprising, in claim 1, an equivalent amount of an isonate-based curing agent of the porous composite elastic film of 110 to 150 g / eq or less. Claim 10 A porous composite elastic film according to claim 1, wherein the catalyst of the porous composite elastic film is included in a weight ratio of 0.1 to 0.001 relative to the isonate-based curing agent. Claim 11 A porous composite elastic film according to claim 1, wherein the hydropolymer comprises 1 to 20% acrylic polymer, 30 to 50% Si polymer (Si Polyoli) and polyol (Polyol), and 10 to 30% silicone. Claim 12 A porous composite elastic film according to claim 1, wherein the porous cells of the right-angled cross-section are closed cells or open cells. Claim 13 A porous composite elastic film according to claim 12, wherein the diameter of the closed cells is 50 to 200 μm and the diameter of the open cells is 10 to 40 μm. Claim 14 A porous composite elastic film comprising a plurality of stress release holes on the surface of the porous composite elastic film according to claim 1. Claim 15 A porous composite elastic film comprising, in the 14th, the diameter of the opening of the stress release hole being 3 to 80 μm. Claim 16 (a) a step of first mixing a hydropolymer, a curing agent, and an isocyanate; (b) a step of second mixing by adding a catalyst and a crosslinking agent after the first mixing of step (a); (c) a step of visually confirming porous cells and casting the second mixture of step (b); and (d) a step of manufacturing a film using a roll-to-roll method after step (c); comprising a method for manufacturing a porous composite elastic film. Claim 17 A method for manufacturing a porous composite elastic film according to claim 16, wherein the secondary mixing of step (b) above comprises making the material uniform. Claim 18 A method for manufacturing a porous composite elastic film according to claim 16, comprising manufacturing it in the form of a thin film after casting in step (c) above.